Clean [compact disc, unabridged] : overcoming addiction and ending America's greatest tragedy - Sheff, David (Brilliance Audio, 2013)
Addiction is a disease; it is preventable and treatable. It is not a moral failing. As with other illnesses, the approaches most likely to work are based on science, not on faith, tradition, contrition, or wishful thinking. Those facts are the foundation of Clean, a new paradigm for preventing drug abuse and treating addiction and the mental illnesses that usually accompany it.